Regulation of international data transfers under EU data protection law - Veronika Stoilova (CES Working Papers, 2021)
This study seeks to identify the specifics of personal data protection in the context of EU legislation. The focus is on the personal data transferred outside the Union. It is described how the EU data protection law provides specific measures in order to ensure the protection of individuals and legal persons from malicious acts. The article also highlights the reform of the EU data protection legislation in the context of the reliability of the data transfer mechanisms to third countries. The legal regulation in this matter goes through various stages of development, and the latter one includes the implementation of rules with a focus on ensuring greater data sharing between institutions and companies. The analysis of the international data flows as a priority topic in relations between the EU and countries outside its borders, including international organizations, also find its place in the study. In this sense, transfers to specific sectors based on specific international agreements will be considered in connection with the improvement and strengthening of the existing procedures for international data transfer.
Keywords: 330; international data transfer; data protection; European Union; legislation reform